2018
DOI: 10.3390/molecules23061443
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Colorimetric Detection of Cartap Residues by AgNP Sensor with Magnetic Molecularly Imprinted Microspheres as Recognition Elements

Abstract: The overuse of cartap in tea tree leads to hazardous residues threatening human health. A colorimetric determination was established to detect cartap residues in tea beverages by silver nanoparticles (AgNP) sensor with magnetic molecularly imprinted polymeric microspheres (Fe3O4@mSiO2@MIPs) as recognition elements. Using Fe3O4 as supporting core, mesoporous SiO2 as intermediate shell, methylacrylic acid as functional monomer, and cartap as template, Fe3O4@mSiO2@MIPs were prepared to selectively and magneticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…The MMIPs were synthesized by the following procedure. The magnetic Fe 3 O 4 particles, Fe 3 O 4 @mSiO 2 particles, and vinyl-modified Fe 3 O 4 @mSiO 2 particles were prepared in turn according to our previously published method [27,28,29], as follows. Firstly, FeCl 3 ·6H 2 O (1.35 g), polyethylene glycol (1.00 g) and sodium acetate (3.60 g) were dissolved in 40 mL of ethylene glycol and ultrasonicated for 30 min to form yellow solution, which was then transferred into a 100 mL dry polytetrafluoroethylene lined autoclave and heated at 200 °C for 8 h. After cooling down, the mixture was washed 3 times by triple distilled water and ethanol, respectively, and then dried in vacuum at 50 °C for 8 h to obtain black Fe 3 O 4 particles.…”
Section: Methodsmentioning
confidence: 99%
“…The MMIPs were synthesized by the following procedure. The magnetic Fe 3 O 4 particles, Fe 3 O 4 @mSiO 2 particles, and vinyl-modified Fe 3 O 4 @mSiO 2 particles were prepared in turn according to our previously published method [27,28,29], as follows. Firstly, FeCl 3 ·6H 2 O (1.35 g), polyethylene glycol (1.00 g) and sodium acetate (3.60 g) were dissolved in 40 mL of ethylene glycol and ultrasonicated for 30 min to form yellow solution, which was then transferred into a 100 mL dry polytetrafluoroethylene lined autoclave and heated at 200 °C for 8 h. After cooling down, the mixture was washed 3 times by triple distilled water and ethanol, respectively, and then dried in vacuum at 50 °C for 8 h to obtain black Fe 3 O 4 particles.…”
Section: Methodsmentioning
confidence: 99%
“…Wu et al reported on the use of NPs with MIPs for the colorimetric detection of residues of the insecticide Cartap in tea [ 224 ]. Cartap was extracted from spiked and non-spiked samples of tea by means of magnetic molecular imprinted microspheres (Fe 3 O 4 @mSiO 2 @MIPs) that utilized methacrylic acid as a functional monomer.…”
Section: Low-cost Mip Assay Formatsmentioning
confidence: 99%
“…Illumination of the filtrate with a simple UV-lamp visually confirms the presence or absence of the target. Adapted with permission from [ 224 ]. Copyright Elsevier 2019.…”
Section: Low-cost Mip Assay Formatsmentioning
confidence: 99%
“…In addition, the molecularly imprinted materials with magnetic components have attracted great attention due to their unique magnetic responsivity, low toxicity, and modifiable surface . Among these nanocomposites, magnetic core‐shell materials together with mesoporous nanostructures are of particular interest since they exhibit high surface area and porosities, excellent chemical and thermal stability . As shown in Figure B, Chen et al prepared a NIR‐light responsive magnetic lysozyme‐imprinted mesoporous microsphere with magnetic components, showing a high saturation adsorption capacity of 700 mg g −1 within 30 min for lysozymes because of the high surface area of 570 m 2 g −1 and the mesopore size of 12 nm.…”
Section: The Currently Popular Imprinting Materialsmentioning
confidence: 99%